Endoscopic vs. Microscopic Transsphenoidal Surgery for the Treatment of Pituitary Adenoma: A Meta-Analysis - Chen, Jia; Liu, Hongyan; Man, Siliang; Liu, Geng; Li, Quan; Zuo, Qingyao; Huo, Lili; Li, Wei; Deng, Wei (Frontiers in Surgery, 2022)
Purpose Currently, endoscopic and microscopic trans-sphenoidal surgery are commonly used surgical options for patients with pituitary adenomas. The purpose of this study is to evaluate the efficacy and safety of these two methods. Methods A computer search of Pubmed, Embase, Cochrane library, Web of Science and Google Scholar databases related to. The deadline is March 01, 2021. Through literature screening, data extraction and literature quality evaluation, the included literature was meta-analyzed using RevMan software 5.1. Results A total of 37 studies including 5591 patients were included. There was no significant difference in gross tumor removal (GTR) and hormone-excess secretion remission (HES remission) between two groups (RR=1.10, 95% CI:0.99-1.22, P=0.07; RR=1.09, 95% CI:1.00-1.20, P=0.05). Endoscopic trans-sphenoidal surgery was associated with lower incidence of diabetes insipidus (RR = 0.71, 95% CI: 0.58-0.87, P = 0.0008) hypothyroidism (RR = 0.64, 95% CI: 0.47-0.89, P = 0.007) and septal perforation (RR = 0.32, 95% CI: 0.13-0.79, P = 0.01) than those with microscopic trans-sphenoidal surgery. Conclusion This meta-analysis found that endoscopic trans-sphenoidal surgery cannot significantly improve GTR and HES remission, but it can reduce the incidence of diabetes insipidus, hypothyroidism and septal perforation without increasing the rate of other complications.